Review – Windows on mathematical meanings - Gjone, Gunnar (NOMAD Nordic Studies in Mathematics Education, 1997)
Noss, R. & Hoyles, C. (1996). Windows on mathematical meanings (Mathematics education library, volume 17). Dordrecht, NL: Kluwer Academic Publishers, 275 p. https://doi.org/10.1007/978-94-009-1696-8